Differences of Bone Marrow Features and BCR-ABL Variants in Chronic Granulocytic Leukemia Post Tyrosine Kinase Inhibitor Therapy - Wivina Riza Devi; M Darwin Prenggono; Purwanto AP; Imam B (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Chronic Granulocytic Leukemia (CGL) occurs due to chromosomal translocation (9;22) known as Philadelphiachromosome. p210 BCR-ABL1 oncogenes are classified into b2a2 and b3a2 transcripts which possibly lead to differentclinical manifestations and response to therapy. This study was aimed to prove that there is a difference in bone marrowfeatures and BCR-ABL between remissive and resistant CGL after Tyrosine Kinase Inhibitor (TKI) therapy. This research wasan observational study with a cross-sectional design carried out at Ulin Hospital Banjarmasin on 32 subjects. BCR ABL wasdetected by using PCR and bone marrow features were assessed by using bone marrow aspiration technique. The differencebetween bone marrow features and BCR-ABL variants was analyzed by using the T-test (p < 0.005) and Chi-Square(p < 0.005), respectively. There was a difference of BCR-ABL variants with p=0.091 and characterized by M:E ratio (p=0.124),myeloblast count (p=0.063), and eosinophil count (p=0.055). Also, there was a difference of bone marrow cellularity(p=0.000) and basophil count (p=0.016) between remissive CGL and resistant CGL patients. There was no difference in BCRABL variants, myeloblast count and eosinophil count between remissive CGL and resistant CGL patients. However, there wasdifferent of bone marrow cellularity and basophil count between remissive CGL and resistant CGL patients.